Let's talk about medication: concordance in rating medication adherence among multimorbid patients and their general practitioners - Ose, Dominik; Mahler, Cornelia; Baudendistel, Ines; Ludt, Sabine; Szecsenyi, Joachim; Freund, Tobias (Patient preference and adherence, 2012)
Medication adherence can be essential for improving health outcomes. Patients with multiple chronic conditions, often receiving multiple medications, are at higher risk for medication nonadherence. Previous research has focused on concordance between patients and providers about which medication should be taken. However, the question of whether patients and providers are concordant in rating actual medication intake has not been answered as yet. This study aimed to explore the extent and predictors of patient – provider concordance in rating medication adherence in patients with multiple chronic conditions.